Associations between brain morphology, inflammatory markers, and symptoms of fatigue, depression, or anxiety in active and remitted Crohn’s disease - Thomann, Anne K.; Schmitgen, Mike; Stephan, Jule C.; Ebert, Matthias; Thomann, Philipp; Szabo, Kristina; Reindl, Wolfgang; Wolf, Robert Christian (Journal of Crohn's and Colitis, 2024)
Fatigue and psychosocial impairments are highly prevalent in IBD, particularly during active disease. Disturbed brain-gut interactions may contribute to these symptoms. This study examined associations between brain structure, faecal calprotectin, and symptoms of fatigue, depression, and anxiety in persons with Crohn’s disease [CD] in different disease states.In this prospective observational study, n = 109 participants [n = 67 persons with CD, n = 42 healthy controls] underwent cranial magnetic resonance imaging, provided stool samples for analysis of faecal calprotectin, and completed questionnaires to assess symptoms of fatigue, depression, and anxiety. We analysed differences in grey matter volume [GMV] between patients and controls, and associations between regional GMV alterations, neuropsychiatric symptoms, and faecal calprotectin.Symptoms of fatigue, depression, and anxiety were increased in patients with CD compared with controls, with highest scores in active CD. Patients exhibited regionally reduced GMV in cortical and subcortical sensorimotor regions, occipitotemporal and medial frontal areas. Regional GMV differences showed a significant negative association with fatigue, but not with depression or anxiety. Subgroup analyses revealed symptom-GMV associations for fatigue in remitted but not in active CD, whereas fatigue was positively associated with faecal calprotectin in active but not in remitted disease.Our findings support disturbed brain-gut interactions in CD which may be particularly relevant for fatigue during remitted disease. Reduced GMV in the precentral gyrus and other sensorimotor areas could reflect key contributions to fatigue pathophysiology in CD. A sensorimotor model of fatigue in CD could also pave the way for novel treatment approaches.
Online veröffentlicht: 17. Mai 2024
Gesehen am 07.01.2025